1995
DOI: 10.1128/jb.177.20.5912-5917.1995
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene (arpU) controlling muramidase-2 export in Enterococcus hirae

Abstract: Muramidase-2 of Enterococcus hirae is a 74-kDa peptidoglycan hydrolase that plays a role in cell wall growth and division. To study its regulation, we isolated a mutant defective in muramidase-2 release under certain growth conditions. This mutant had cell walls which apparently lacked 74-kDa muramidase-2 but which accumulated two proteolytic fragments of 32 and 43 kDa, which exhibited muramidase-2 activity in the membrane fraction. By complementation cloning, we identified a 2.6-kb fragment of the E. hirae ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…ArpU was described as a regulator of cellular muramidase-2 of Enterococcus hirae (18), and no additional work with this protein has been reported. Although initially described as a chromosomally encoded gene, analyses of the sequences in the database clearly demonstrate that ArpU homologues are phage-encoded (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…ArpU was described as a regulator of cellular muramidase-2 of Enterococcus hirae (18), and no additional work with this protein has been reported. Although initially described as a chromosomally encoded gene, analyses of the sequences in the database clearly demonstrate that ArpU homologues are phage-encoded (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the genetic comparison revealed that gene mutations were identified in dprA and arpU . The former gene was described as a competence gene involved in the protection of incoming DNA, and the latter gene was a transcriptional regulator that plays a role in cell wall growth and division [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…ArpU was reported to control the muramidase-2 export, which plays an important role in cell wall growth and division. Mutation of arpU may lead to serious metabolic effects [ 43 ]. The transcriptome and proteome analysis suggests that the differentially expressed genes and proteins are mainly distributed in pathways involved in glycometabolism, lipid metabolism, amino acid metabolism, predicted general function, energy production and conversion, replication, recombination and repair, cell wall, membrane biogenesis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them were to differentiate between E faecalis and E faecium. The mur-2 gene codes for a 74-kDa peptidoglycan hydrolase that plays a role in the cell wall growth and division [19]. The gene was cloned, sequenced, and used to specifically identify E hirae from other enterococcus.…”
Section: Discussionmentioning
confidence: 99%